Interaction between Pseudomonas stutzeri MJL19 and soybean plants in saline stress - Lami, María Jesús (2019)
Surrounding plants roots, there is a highly complex ecosystem; influenced by both, root secretions and metabolic activity of microorganisms.During colonization and adaptation stage in the rhizosphere, bacteria modify their pattern of gene expression such as metabolism, mobility, chemotaxis, EPS synthesis and secretion, in order to reach an adaptive mechanism for the interaction with the plant.The interaction of the bacterium P. stutzeri MJL19 with soybean root was studied through a transcriptomic analysis of genes potentially related to colonization and abiotic stress conditions. The expression was detected by RT-qPCR of colonization involved genes: algA, bcsA, oprF, clpP, bcsA, putA and putP, also stress related genes: dnaJ, proC and sodC. dnaJ, other chaperones that participate in the proper folding of stress-damaged proteins and the stabilization of other cellular proteins and finally we determine the expression of some proC, sodC and dnaJ protective osmolytes.clpP, oprF, algA, bcsA, putA and putP showed greater expression in populations of MJL19 attached to soybean root grown in saline conditions respect to the situation in the absence of the plant root. In the case of clpP and oprF the difference in root expression was about 5 times greater in the saline condition with respect to the non-saline. In contrast, the NaCl did not generate significant changes in the expressions.The expression of genes related to abiotic stress dnaJ and proC, showed greater expression in populations of MJL19 attached to the soybean root in saline stress, on the other hand sodC under the expression in this condition.In P. stutzeri MJL19 the genes related to the colonization and formation of biofilms such as oprF, clpP, algA and bcsA are expressed in the presence of soybeans in a condition of saline stress, indicating that the bacterium grows as a biofilm when it is in the presence of the root of soy. The gene involved in the proline biosynthesis, proC, is not expressed in the analyzed strain grown in the presence of soybean roots. On the other hand, the proC genes were expressed in strains grown in cultures supplemented with NaCl. Therefore MJL19 regulates the synthesis of proline in a saline condition; in the presence of the plant it does not produce it, possibly due to the use of plant exudated proline. The genes dnaJ and sodC, are not active in the presence of soybean roots and NaCl separated, although the expression is observed in stains with the plant in saline stress.